Buddhist Integration to Strengthen the Sangha Activities of the Sangha Leaders of Samut Prakan Province - Sommuk Samahito, Phravachirathamvithan (Mahachula Academic Journal, 2025)
In this research, the objectives were purposely made: 1) to study the current state of Sangha administration in Samut Prakan Province, 2) to study the Buddhist principles for strengthening Sangha affairs, and 3) to develop the DHARMA-6 Model as a framework for Buddhist integration in Sangha administration. A qualitative research design was employed through in-depth interviews with 14 key informants and focus group discussions with 13 participants. Content analysis was applied to synthesize knowledge and construct the model accordingly. (1) The findings showed that Sangha administration comprises of six key dimensions: governance, religious education, propagation, public utilities, educational welfare, and public welfare. Public welfare demonstrated the highest level of integration and effectiveness, while religious education, though strong in some aspects, lacked comprehensive integration at the provincial level where the highest uniqueness and effectiveness of such administration are still awaited to obtain. (2) Buddhist principles were systematically applied across these dimensions, including 7 kinds of Aparihãniyadhamma (unity and sustainability in governance), 3 kinds of Threefold Training or Trisikkhã (development of religious education and successors), 4 kinds of Saṅgahavatthu (support for educational welfare and community networking), Buddhist teaching methods (effective propagation), 4 kinds of Brahmavihãra (compassion and loving-kindness in public utilities), and 6 kinds of Sãraṇĩyadhamma (harmony and solidarity in public welfare). (3) The DHARMA-6 Model integrates these principles into a comprehensive framework consisting of six components: Dhamma Integration, Holistic Development, Administrative Leadership, Religious Education, Management Innovation, and Alliance Collaboration. Guided by the principle of “Developing People before Developing Infrastructure,” the model emphasizes the Trisikkhã as the foundation for producing qualified successors, supported by governance based on Aparihãniyadhamma. This integrated approach enables the Sangha to achieve unity, enhance institutional capacity, and ensure sustainable service to both the Buddhist community and society at large.